The HbA1c/HDL-C ratio as a screening indicator of NAFLD in U.S. adults: a cross-sectional NHANES analysis (2017–2020) - Ju Wu; Wenjing Yu; Linglong Huang; Shuangshuang Hou; Yanan Huang; Zhihua Huang; Zhiyuan Dai; Jiajun Yin; Zhequn Nie (BMC Gastroenterology)
Abstract Background Non-alcoholic fatty liver disease (NAFLD), a metabolic liver disorder closely associated with obesity and diabetes, urgently requires early screening. This population-based study is the first to explore the relationship between glycemic control and a novel dyslipidemia composite index—the glycated hemoglobin/high-density lipoprotein cholesterol (HbA1c/HDL-C) ratio in individuals with NAFLD and liver fibrosis. Methods Data from 5,891 adults in the 2017–2020 National Health and Nutrition Examination Survey (NHANES) were analyzed. Binary logistic regression and restricted cubic spline (RCS) analyses were used to evaluate the association between HbA1c/HDL-C ratio and the risk of NAFLD and liver fibrosis. The reliability of the results was confirmed using subgroup, interaction, and sensitivity analyses. Screening performance was assessed using receiver operating characteristic (ROC) curves, and differences between various indicators were compared using the DeLong test. Results After adjusting for confounding factors, each 1% increase in the HbA1c/HDL-C ratio was associated with a 20% higher risk of NAFLD (odds ratio [OR] = 1.20, 95% confidence interval [CI]: 1.14–1.27, P < 0.001). Sensitivity analyses confirmed the robustness of these findings (P < 0.001). However, the associations with liver fibrosis (P = 0.064) and moderate-to-severe liver fibrosis (P = 0.130) were not statistically significant. Participants in the highest HbA1c/HDL-C quartile had significantly higher odds of NAFLD than those in the lowest quartile (OR = 2.21, 95% CI: 1.74–2.79). RCS analysis revealed a non-linear positive correlation between the HbA1c/HDL-C and NAFLD risk (P for non-linear = 0.003). Subgroup and interaction analyses showed that this association was more pronounced in the non-diabetic population. The ROC curve yielded an AUC of 0.713 for NAFLD screening. Conclusion In U.S. adults, the HbA1c/HDL-C appears to be an effective tool for NAFLD screening. As a novel composite index, it also holds considerable reference value for identifying NAFLD risk in the non-diabetic population.